Unveiled Crucifix taken back to the Altar of Repose - Mumbai Archive Project Team (Jio Institute, 2024)
The unveiled crucifix is reverently taken back to the Altar of Repose, marking the conclusion of the Eucharist ceremony. A cross-bearer leads the procession, followed by two servers carrying lighted candles. Father Vernon Aguiar, acting rector of the basilica since 2023, follows at the end.